Protótipos e réplicas na representação da arquitetura - Cattani, Arq. Airton (Universidad Nacional del Litoral, 2013)
Prototypes and replicas are resources with the greatest similarity to the planned or original construction, and are highly important elements for understanding the spatial characteristics of architecture. This article presents reflections on the use of this kind of physical model, which particularly for financial reasons is rarely used to provide a prior view of architecture.